2010
DOI: 10.1021/jf101277t
|View full text |Cite
|
Sign up to set email alerts
|

A Major Green Tea Component, (−)-Epigallocatechin-3-gallate, Ameliorates Doxorubicin-Mediated Cardiotoxicity in Cardiomyocytes of Neonatal Rats

Abstract: Cardiac injury is a major complication of the oxidative stress-generating anticancer drug doxorubicin (DOX). The green tea polyphenol (-)-epigallocatechin-3-gallate (EGCG) has been reported to play a cardioprotective role in diseases associated with oxidative stress. The objective of this study was to investigate whether EGCG can protect against DOX-induced toxicity in cardiomyocytes. The data showed that EGCG protected the cardiomyocytes from DOX-mediated cardiotoxicity, as evidenced by decreased lactate dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 32 publications
2
27
0
1
Order By: Relevance
“…16 Other studies emphasize EGCG's antioxidant properties by demonstrating cardioprotection against doxorubicin, an anthracyline aminoglycoside, by attenuating ROS production and increasing expression of endogenous antioxidant enzymes. 17,18 In the present study, co-administration of gentamicin with atRA potentiated hair cell loss and death.…”
Section: Discussionsupporting
confidence: 58%
“…16 Other studies emphasize EGCG's antioxidant properties by demonstrating cardioprotection against doxorubicin, an anthracyline aminoglycoside, by attenuating ROS production and increasing expression of endogenous antioxidant enzymes. 17,18 In the present study, co-administration of gentamicin with atRA potentiated hair cell loss and death.…”
Section: Discussionsupporting
confidence: 58%
“…Decreased ROS and MDA levels together with increased expression and activity of antioxidant enzymes showed that induction of the antioxidant defense contributed to the protective effect. 44,45 Moreover, EGCG was shown to improve Ca 2þ handling in DOX-treated cells. 45 Hence, this green tea polyphenol may reverse DOX-induced intracellular Ca 2þ depletion and contribute to the maintenance of contractile function.…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…Various in vivo studies have confirmed that EGCG mitigates doxorubicin-induced cardiotoxicity by suppressing oxidative stress (6063). The oxygen free radical scavenging ability of EGCG has been demonstrated to protect cardiomyocytes from doxorubicin-mediated cardiotoxicity according to histopathological analysis (64).…”
Section: Discussionmentioning
confidence: 99%